In‐Situ Photometric Properties of Lunar Regolith Revealed by Lunar Mineralogical Spectrometer on Board Chang'E‐5 Lander. Issue 4 (15th February 2022) - Xu, Jiafei; Wang, Meizhu; Lin, Honglei; Xu, Xuesen; Liu, Bin; Yan, Wei; Yang, Yazhou; Wang, Rong; Liu, Chengyu; Xu, Rui; He, Zhiping
Abstract: The photometric properties of the uppermost lunar regolith are used in the spectroscopic study. China's Chang'E‐5 (CE‐5) mission successfully landed in the Northern Oceanus Procellarum of the Moon, carrying the scientific payload lunar mineralogical spectrometer (LMS). LMS performed full‐view scanning and obtained the reflectance spectra in various geometric configurations. The photometric properties, including the single‐scattering albedo ω and two parameters of the Henyey‐Greenstein phase function ( b, c ), were derived. Our modeling results showed weak backward scattering and strong forward scattering properties of the regolith at the CE‐5 landing site. Meanwhile, the asymmetry parameter ( − b × c ) (-b× c) indicates that CE‐5 regolith has weaker forward scattering than the Apollo lunar soil samples and the regolith at the Chang'E‐4 landing site. The derived Hapke parameters can be used for comparison with that of the returned lunar sample, supporting further studies of lunar spectroscopy, and can be the ground truth of the CE‐5 landing area. Plain Language Summary: The in‐situ mineral compositions of the lunar regolith can be retrieved using spectral observations with known photometric properties of the lunar surface. The lunar mineralogical spectrometer installed on the Chang'E‐5 lander conducted in‐situ full‐view scanning, and obtained many spectral data. We derived a photometric function using these data to study the properties of the regolith. These findings can be compared to the measured value of the lunar returned samples of CE‐5 to support future spectroscopy research and provide a better understanding of the mineralogical information at the CE‐5 landing area. Key Points: The photometric properties of the lunar regolith are revealed by in‐situ spectrum data from the Chang'E‐5 Lunar Mineralogical Spectrometer The derived photometric parameters contribute to a better understanding of the properties of the regolith on the near side of the moon The forward scattering was dominant in the landing site, consistent with the compositions of the lunar samples returned from the Chang'E‐5